2021
DOI: 10.1007/s10072-021-05045-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID-19 pandemic and the lockdown measures on the local stroke network

Abstract: Introduction The COVID-19 outbreak highly impacted the acute ischemic stroke care management. The primary end point of the study was to evaluate the impact of the COVID-19 outbreak and the following lockdown measures on our hub-and-spoke network; the secondary end point was to evaluate if the impact of the COVID-19 outbreak was different in hub-and-spoke centers. Methods This was a retrospective multicenter observational study conducted at the Stroke Units of Policlinico Gemelli, Ospedale San Filippo Neri, Osp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 17 publications
2
20
1
1
Order By: Relevance
“…On the other hand, while our IVT rate was stable (23.8% vs 24.3% vs 20.6%), which was in contrast to other observations [13,[17][18][19], but in line with the nationwide German cohort study [8], the rate of large vessel occlusion dropped not significantly along with a significant reduction of our EVT rate and absolute number between 2019 and the spring lockdown of EVT by 58 and 62%, respectively. Our observed reduction of EVT is beyond the 21% decline reported from a registry in France [20] or the 23% decline reported from China [9].…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, while our IVT rate was stable (23.8% vs 24.3% vs 20.6%), which was in contrast to other observations [13,[17][18][19], but in line with the nationwide German cohort study [8], the rate of large vessel occlusion dropped not significantly along with a significant reduction of our EVT rate and absolute number between 2019 and the spring lockdown of EVT by 58 and 62%, respectively. Our observed reduction of EVT is beyond the 21% decline reported from a registry in France [20] or the 23% decline reported from China [9].…”
Section: Discussionsupporting
confidence: 58%
“…This may be related to possible delayed hospital arrival and an overall decrease in the absolute number of patients with mild and moderate stroke seeking medical care. 21,29,30,46,54,55,59,60,62,70 However, the likelihood of being treated with IVT did not differ between two periods in comprehensive stroke centers and that of being treated with EVT increased during the pandemic, which might be due to adequate changes made in workflow of acute stroke care in comprehensive stroke centers. 71 Higher likelihood of being treated with EVT might also have been caused by higher likelihood of large vessel occlusions due to prothrombotic state driven by COVID-19 virus, as reported by multiple studies.…”
Section: Discussionmentioning
confidence: 94%
“…8, Twenty-four studies met criteria for 'good' quality and 13 met criteria for 'fair' quality (Supplemetary Tables 2-4). Most studies compared the pandemic period (ranging from January to June 2020) to a similar period in the preceding year (range January to June 2019) [28][29][30][31]33,35,39,[41][42][43]45,46,[48][49][50]52,[54][55][56][57][58]60 or the months preceding the pandemic (range September 2019 to December 2019). 8,32,34,[36][37][38]40,44,47,51,53,59,[61][62][63]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some studies have shown that performance of stroke care declined during the pandemic, with increases in door-to-needle and door-to-groin times, and a reduction of intravenous thrombolysis and endovascular therapy procedures. 18 , 26 , 27 , 28 , 29 In one study, delays in stroke therapy were related to increased time from symptom detection to hospital arrival. 30 These findings underline the hypothesis that the drop in stroke admissions probably reflect increased barriers to stroke care.…”
Section: Discussionmentioning
confidence: 99%